Zad. 4
Zapisz wyrażenia nie używając nawiasów, a następnie zredukuj wyrazy
podobne:
a) (a2 + a3-5a ) + ( a3 - a2 - 3a) - (-a3 - a2 - 4a)
b) 2(x3 - X2 - 7x - 10) - X ( x2 - 3x-5)
c) (z - 4) (z +5)
d) (y - 3) (y2 - 5y + 7)


Odpowiedź :

Odpowiedź:

a)  ( a²+a³ -5a) + ( a³-a²-3a) - ( -a³-a²-4a)= a²+a³-5a + a³-a²-3a +a³+a² +4a=

                         = a²+3a³-4a

b)   2 ( x³-x²-7x -10) - x (x²-3x -5 )= 2x³-2x²-14x -20 -x³+3x²+5x= x³+x²-9x-20

c)   (z-4 ) (z+5)= z²+5z -4z -20= z²+z -20

d)     ( y -3) (y ²-5y +7)= y³-5y²+7y -3y²+15y-21= y³-8y²-21

Szczegółowe wyjaśnienie:

Viz Inne Pytanie